The role of parents’ beliefs regarding their children’s literacy acquisition - Ratka-Pauler, Anna; Birnbaum, Lisa; Kröner, Stephan (Frontiers in Education, 2024)
Early literacy acquisition is influenced by children's social and cultural background. Several empirical studies have shown that by considering literacy activities at home and by providing cultural resources, the correlation between the social and cultural background and the children's literacy achievement can be significantly reduced. This suggests a crucial importance of parents' beliefs and their role as active agents in the acquisition of literacy skills at homeTherefore, parents as active agents in home literacy acquisition and their beliefs are crucial. The aim of the present paper study is therefore to provide an overview of the range of relevant parental attitudes on the parents' beliefs towards joint literacy activities. In an elicitation study based on the theory of planned behavior, the statements of N = 25 German parents of pre-preschool and preschool children were recorded. All deductive categories based on the theory of planned behavior could be addressed, furthermore the category system could be differentiated inductively. tThus the parental beliefs about joint literacy activities were comprehensively mapped. It is discussed, how the explorative results of this study can be used in further studies, for example, to generate a questionnaire based on the TPB to assess parental beliefs for joint literacy activities.